Food Plans as a Platform to Amplify Food Justice - Bury, Anna. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Kristin Skrabut.; Committee: Julian Agyeman.; Keywords: Urban planning, Environmental justice, and Public policy.